2020
DOI: 10.1016/j.knee.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of walking with a modified gait on activation patterns of the knee spanning muscles in people with medial knee osteoarthritis

Abstract: To evaluate muscle activation patterns and co-contraction around the knee in response to walking with modified gait patterns in patients with medial compartment kneeosteoarthritis (KOA). Design: 40 medial KOA patients walked on an instrumented treadmill. Surface EMG activity from seven knee-spanning muscles (gastrocnemius, hamstrings, quadriceps), kinematics, and ground reaction forces were recorded. Patients received real-time visual feedback on target kinematics to modify their gait pattern towards three dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…Other emerging treatment paradigms for knee OA focus on gait retraining through the use of simple instruction to change foot progression angle, alter step width or medialise the knee position [ 89 ]. However, while these approaches have been shown to reduce the load on the medial compartment [ 89 ], they are associated with muscle overactivity [ 90 ]. In contrast, Cognitive Muscular Therapy was specifically designed to reduce elevated muscle activity.…”
Section: Discussionmentioning
confidence: 99%
“…Other emerging treatment paradigms for knee OA focus on gait retraining through the use of simple instruction to change foot progression angle, alter step width or medialise the knee position [ 89 ]. However, while these approaches have been shown to reduce the load on the medial compartment [ 89 ], they are associated with muscle overactivity [ 90 ]. In contrast, Cognitive Muscular Therapy was specifically designed to reduce elevated muscle activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that there was a significant correlation between AT thickness and KOA severity ( Elbaz et al, 2017 ), and a diminished phase shift was detected between medial and lateral gastrocnemius activation in severe KOA patients during walking ( Rutherford et al, 2011 ). GM is one of the knees’ spanning flexor muscles, of which activation could affect knee adduction moment ( Booij et al, 2020 ), which was a reliable and accurate measurement of load exerted on the medial compartment of the knee joint, and had been proven to be highly related to the KOA severity ( Khan et al, 2018 ). Meanwhile, it was suggested that foot posture was related to the foot center of pressure and could affect the knee adduction moment by the mediolateral center of pressure shift ( Solomonow-Avnon et al, 2019 ), subsequently exerting an impact on KOA.…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that reducing KAM with gait modi cations does not necessarily also change medKCF because other joint loading parameters as KFM or muscle co-contraction might be affected 11,30,31 . A possible successful gait modi cation for reducing medKCF could be in-toeing that potentially reduces KAM but not substantially affecting KFM [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%